Aesthetic Complex Management of Four Upper Anterior Teeth - Asri Riany Putri; Ilma Yudistian; Arya Kusuma Agraha; Dwis Syahriel (Fakultas Kedokteran Gigi, Universitas Mahasaraswati Denpasar, 2025)
Introduction: Anterior teeth require special attention in terms of aesthetics. Complex aesthetic treatment becomes the main choice in cases of anterior teeth with more than one caries, deformities, malposition and in needs of root canal treatment. Case: A 49-year-old female patient complained of broken upper right and left front teeth due to impact. Objective examination found that the lingual margins of teeth 11, 12 and 13 appeared reddish and bled easily, composite fillings with secondary caries at 21 dentin depths and 22 pulp depths, chipping at 11, 12 and 22. Percussion of tooth 22 (+), pressure test (-) and CE (+). Case Treatment: One visit root canal treatment in 22, direct composite veneer in 11, 21, 22 and composite restoration in 12. Discussions: Complex aesthetic treatment involves more than one anterior tooth that requires root canal treatment as well as correction of shape and position. Determination of shape, tooth proportion, color, position dimension, inclination, smile position and lip line, relationship between teeth, relationship of facial midline to lip midline are required in complex aesthetic treatment. Composite resin is chosen as a restorative material due to aesthetic considerations, faster procedure, low cost, does not take much of healthy tooth structure, easy to be repaired when there is damage and does not damage the opposing teeth. The use of palatal putty index can increase the efficiency of the work and maximize the final result. Conclusion and Suggestions: Complex aesthetic treatment using direct composite veneer is a fast, low-cost treatment option that can provide good aesthetic results in cases of four malformed and malpositioned upper anterior teeth.